A primary mediastinal germ cell tumor of yolk sac type: case report - Darif, Khadija (Pan Afr Med J, 2021)
The mediastinal malignant germ cells tumor represents less than 0.5% of thoracic tumors, although the mediastinum is one of the main extragonadic locations of these tumors. In the majority of cases, young people are those most affected. The prognosis of mediastinal malignant germ cells tumors is poor, especially non-seminomatous germ tumors. In this article, we report a rare case of a young 19-years-old patient treated for a mediastinal germ cell tumor of yolk sac. The patient presented a chest pain; the chest computed tomography (CT) showed a right paramedian mediastinal mass with a pleural effusion associated with supraclavicular and cervical lymph nodes. Biopsy revealed a non-seminomatousgerm cell tumor of yolk sac. The exams showed elevated alpha-fetoprotein (AFP), without any meaningful elevation of other serictumor markers. The patient received 4 cycles of chemotherapy based on etoposide, ifosfamide and platinum salts then a complete excision of the mass.